Aggregatibacter aphrophilus spinal epidural abscess. Issue 7 (16th July 2020) - Altdorfer, Antoine; Gavage, Pierre; Moerman, Filip
Abstract : A 76-year-old woman with a rare case of spinal epidural abscess (SEA) that had no risk factors for such type of infection, presented symptoms of back pain, progressive neurological deficit of the lower limb and loss of sphincter control. A gadolinium-enhanced MRI confirmed the diagnosis of an SEA. The patient underwent laminectomy with surgical drainage, where cultures showed the presence of Aggregatibacter aphrophilus, a bacterium of the HACEK group ( Haemophilus species, Aggregatibacter species, Cardiobacterium hominis, Eikenella corrodens, and Kingella species), rarely involved in SEA. Following surgery, the patient was treated with intravenous ceftriaxone for 6 weeks, and this gave excellent results.